Letter (copy) : Luncheon - 11 March 1937 - Citrine, Walter, 1887-1983
021-0096-001 WMC/EAB/501 International. 26th February 1937. J. Meyer Esq., St. Ermins Restaurant, St. James Park, LONDON. S.W. 1. Dear Sir, LUNCHEON - 11 MARCH 1937. I desire to thank you for your letter of the 25th instant submitting specimen menus for the proposed Luncheon Party on the 11th March next, and to confirm the arrangement made with you over the telephone this afternoon that you will provide a luncheon at four shillings per head as per your specimen menu quoted at four shillings and sixpence, with the exception that there will be a choice of Melon frappe or Creme Portugaise. It is anticipated that the Party will number between 120 and 200 persons, but more definite information will be conveyed to you on this point at a later date. It is desired that the luncheon should start at 1 p.m. Yours sincerely, General Secretary 292/946/21/96